A Theoretical Calculation Method of the Unsupported Span for the Shallow Tunnel in the Soft Stratum - Xiaoxu Tian; Zhanping Song; Guannan Zhou; Xiaowei Zhang (Advances in Civil Engineering)
During the construction of the tunnel in soft stratum, it is often found that the unsupported span is too large, resulting in instability of the tunnel face and collapse of the vault. However, the unsupported span was often selected according to the experience of engineers in the actual construction process, which was lack of the theoretical basis. Therefore, based on the calculation model of the surrounding rock pressure of shallow buried tunnel, this paper analyzed the stability of the tunnel face and the vault and then obtained the calculation formula of the unsupported span of the shallow buried tunnel in soft rock stratum. It was pointed out that the unsupported span is not determined by the arch crown stability or the tunnel face stability alone, but by both. The rationality of the formula was verified by a centrifugal test and an engineering case. The analysis and discussion showed that the unsupported span is sensitive to the cohesion and internal friction angle of the rock-soil mass, especially the cohesion. The unsupported span of the shallow buried tunnel in the soft rock stratum is a linear function of the support pressure. The support pressure has a more significant contribution to the increase of the unsupported span by the centre cross diaphragm (CRD) method, and the unsupported span increases linearly with the increase of the support pressure. The research results provide a theoretical reference for the determination of the unsupported span for the shallow tunnel in the soft stratum.